Relato de experiência: estratégias pedagógicas com estudantes com Transtorno do Espectro Autista - Barbosa, Giulia Vieira Lopes (Universidade Federal de São Carlos, 2024)
The aim of this research is to share and analyze pedagogical strategies experienced in the school context involving the participation of students with Autism Spectrum Disorder (ASD). Based on reports of experiences accumulated throughout the years of undergraduate studies and internships, we seek to discuss pedagogical strategies that promote teaching and learning, highlighting the active participation of students with autism in basic education. Based on Vygotsky's Historical-Cultural Theory, the work emphasizes the importance of social mediation and the historical context of cultural evelopment, considering the particularities and singularities of the students within the school community. The results point to the importance of implementing pedagogical strategies that consider the particularities of the community and promote potential in the process of schooling of students.
Experience report: pedagogical strategies with students with Autism Spectrum Disorder
Keywords: Estratégias Pedagógicas; Transtorno do Espectro Autista; Inclusão Escolar; Pedagogical Strategies; Autistic Spectrum Disorder; School Inclusion; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO